The Effect of Business Strategy, Managerial Ability, Multiple Large Shareholders, and Earnings Management on Investment Efficiency - Elisabeth Andra Wilna Sopacua; Sansaloni Butar Butar (Jurnal Akuntansi Bisnis, 2023)
Companies often withhold or reject projects that generate net present value. As a result, investment decisions are not optimal and lead to lower investment efficiency. This study examines the effect of business strategy, managerial ability, multiple large shareholders, and earnings management on investment efficiency. The sample was selected from companies listed on the Indonesia Stock Exchange for 2019-2021. Financial and insurance industry companies were excluded because they have different accrual characteristics. Several control variables are added to the regression model. The results show that business strategy is associated with investment efficiency. In contrast, managerial ability, multiple large shareholders, and earnings management have no effects on investment efficiency. As for control variables, operating cash flow, debt-to-equity ratio, firm size, and return on assets are associated with investment efficiency.